2019
DOI: 10.3390/app9091735
|View full text |Cite
|
Sign up to set email alerts
|

Air Purification Performance of Photocatalytic Concrete Paving Blocks after Seven Years of Service

Abstract: This paper presents the results of laboratory tests on photocatalytic pavement blocks from a bicycle lane in Poland after seven years of service. Air purification performance was tested on dusty and clean samples using different light sources and setups, with non-laminar gas circulation. Secondary Electrons Secondary Ions (SESI) and InLens detectors combined with SEM–EDS and X-ray analyses were applied to confirm the presence of TiO2 in the studied blocks. The obtained results show that TiO2 was present in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…One of the most important aspect of photocatalytic functional construction materials is retaining their photocatalytic efficiency over time for both photodegredation of air pollutants and self-cleaning characteristics. There are a number of researchers exploring the long-term photocatalytic efficiency of concrete paving blocks and self-cleaning surfaces in in-site applications, in which most of them reported a decrease in the photocatalytic performance of the TiO 2 /cement composites [186,187,188,189,190]. In general, after an interval of four months, the photocatalytic efficiency of TiO 2 -based cementitious materials decreased significantly for both TiO 2 coatings and TiO 2 implemented in concrete bulk [191,192].…”
Section: Influential Parameters On Photocatalysis Efficiencymentioning
confidence: 99%
“…One of the most important aspect of photocatalytic functional construction materials is retaining their photocatalytic efficiency over time for both photodegredation of air pollutants and self-cleaning characteristics. There are a number of researchers exploring the long-term photocatalytic efficiency of concrete paving blocks and self-cleaning surfaces in in-site applications, in which most of them reported a decrease in the photocatalytic performance of the TiO 2 /cement composites [186,187,188,189,190]. In general, after an interval of four months, the photocatalytic efficiency of TiO 2 -based cementitious materials decreased significantly for both TiO 2 coatings and TiO 2 implemented in concrete bulk [191,192].…”
Section: Influential Parameters On Photocatalysis Efficiencymentioning
confidence: 99%
“…After sunset, the abatement of NO x pollutant was nearly zero, and the difference in gas concentration was the result of achieving an equilibrium of gas concentration in the measuring system. Additionally, photocatalytic concrete's ability to reduce NOx levels was measured with a test method described by Witkowski et al [29] with an artificial light source. Artificial UV light was provided with an OSRAM Vitalux 300W with nominal 13.6 W UV-A (315-400 nm) and 3.0 W UV-B (280-315 nm).…”
Section: Results Of the Novel Test Methodsmentioning
confidence: 99%
“…Witkowski et al [29] was applied as a base setup in this study. A general scheme of the method is presented in Figure 9.…”
Section: Removal Of Nitric Oxides By Photocatalytic Materials-novel Tmentioning
confidence: 99%
“…From 2000 to 2010, only two studies were conducted in which TiO 2 photocatalysts were mixed with concrete and cement [ 31 , 32 ]. However, seven studies were conducted from 2010 to 2020 [ 29 , 33 , 34 , 35 , 36 , 37 , 38 ]. These studies mainly focused on road pavement materials, exterior materials, and roof finishing materials.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al investigated the effect of exhaust gas decomposition by setting the UV irradiance as 26.7 W/m 2 , which is the average outdoor illumination, and it was confirmed that exhaust gas decomposition can be achieved when the nano-TiO 2 content is 8% [ 37 ]. Witkowski et al conducted NO removal experiment using a photocatalytic pavement block used for 7 years on a silver bicycle road, and the NO gas reduction performance was investigated by applying 300 W of light; scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) mapping analyses were performed to confirm TiO 2 mixing in the pavement block [ 38 ]. The irradiance of UV applied in the experiment was very high compared with the atmosphere; therefore, the actual environment should be considered while conducting the experiment.…”
Section: Introductionmentioning
confidence: 99%